Keberlanjutan, Konsep Ekonomi Sebagai Filosofi Kehidupan - Pratiwi Nila Sari; Khomsiyah Khomsiyah (Jurnal Kajian Ilmiah, 2023)
The concept of sustainable development is not only related to human welfare but also to the world in which humans live, therefore the concept of sustainable development can be understood as an economic philosophy that includes classical philosophical prospects and harmonizes and integrates economic, socio-political and ecological systems activities. The scope of this research includes an analysis of the philosophical meaning of the concept of sustainable development, with a focus on disclosing the synergy of sustainability and the economic concept in which there are perspectives of anthropocentrism, ecology and utilitarian theory. The writing of this article uses the literature review method based on relevant research journals and documents.